Modeling of 3D plastic anisotropy and asymmetry of extruded magnesium alloy and its applications in three-point bending. (July 2020) - Li, Fei-Fan; Fang, Gang
Abstract: In this paper, three-dimensional (3D) plastic anisotropy, tension-compression asymmetry and their evolutions of as-extruded Mg–Al–Zn-RE alloy are fully characterized. To account for both the anisotropy and asymmetry, Yoon2014 function based on the second and third stress invariants is adopted. In addition, the second stress invariant-based Hill48 function is formulated whereby the relationship between Hill48 and Yoon2014 is explicitly revealed. A total of twelve groups of uniaxial tension and compression tests in three principal planes are conducted, and a complete experimental database for robust model calibration and effective model assessment is obtained. To settle the existing controversial issue on whether the neutral layer shifts to the compressive zone or the tensile zone of a bent magnesium alloy plate, experiments and simulations of three-point bending are performed. A pixel-based matching method is proposed to acquire the specific position of the neutral layer at any stage of bending deformation. It is found that the neutral layer shifts first to compressive zone, then to tensile zone, and finally to compressive zone again during the whole deformation. This finding is also accurately predicted by Yoon2014 model. Based on a comparative analysis of simulation results by Yoon2014 and Hill48 models, the reason for the unique three-stage pattern of the neutral layer shift in magnesium alloy bending is provided. Highlights: Plastic anisotropy and tension-compression asymmetry of as-extruded Mg alloy are characterized in three principal planes. Stress invariant-based Hill48 function is formulated whereby the relation between Hill48 and Yoon2014 is explicitly revealed. Effects of the third stress invariant on plastic yielding are demonstrated by comparisons between two constitutive models. Three-stage pattern of the neutral layer shift during Mg alloy plate bending is discovered by a pixel-based matching method. Comparative analysis indicates that tension-compression asymmetry causes the shift of the neutral layer to tensile zone.